Tugas Room Attendant pada Pembersihan Kamar di Hotel 88 Kedungsari Surabaya - Ikbal Maulana; Reno Aditya Prastyo; Sudono Noto Pradono (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the duties of room attendants in the room cleaning process at Hotel 88 Kedungsari Surabaya, including work procedures, the implementation of cleanliness standards, challenges encountered, and the role of training and supervision in improving service quality and overall guest satisfaction. This research employs a qualitative method with a direct observation approach. The findings indicate that the duties of room attendants are carried out through systematic work stages, starting from preparation, cleaning, to final inspection and worksheet completion as a work control tool. The implementation of strict cleanliness standards is a key factor in maintaining room quality and guest comfort. Despite various challenges such as time constraints, room conditions, and physical fatigue, room attendants are able to perform their duties professionally through effective work management. Furthermore, the role of room attendants is crucial in enhancing guest satisfaction, supported by continuous training and supervision. Therefore, the quality of room attendants’ performance significantly contributes to the image and service quality of the hotel.